1989
DOI: 10.1111/j.1365-2125.1989.tb03516.x
|View full text |Cite
|
Sign up to set email alerts
|

The increase in urinary excretion of 6 beta‐hydroxycortisol as a marker of human hepatic cytochrome P450IIIA induction.

Abstract: 1. Urinary excretion of 6 beta‐hydroxycortisol, hepatic microsomal cortisol 6 beta‐hydroxylase and the specific content of several forms of cytochrome P450 were measured in 8 to 14 patients before and after treatment with rifampicin (600 mg orally per day for 4 days). 2. Rifampicin treatment produced an average five fold increase in daily excretion of urinary 6 beta‐hydroxycortisol. 3. Cortisol 6 beta‐ hydroxylase activity increased from 15 +/‐ 6 pmol min‐1 mg‐1 in organ donors (considered as 'control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
157
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(170 citation statements)
references
References 63 publications
(89 reference statements)
12
157
1
Order By: Relevance
“…The effects on quinidine metabolism found in this study are readily explainable by a rifampicin mediated induction of hepatic CYP3A4. Cortisol metabolic ratio increased 5 times in this study, strongly indicating an induction of hepatic CYP3A4 (Ged et al 1989). The magnitude of the effects in this study are similar to those found by Twum-Barima & Carruthers (1 98 1).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The effects on quinidine metabolism found in this study are readily explainable by a rifampicin mediated induction of hepatic CYP3A4. Cortisol metabolic ratio increased 5 times in this study, strongly indicating an induction of hepatic CYP3A4 (Ged et al 1989). The magnitude of the effects in this study are similar to those found by Twum-Barima & Carruthers (1 98 1).…”
Section: Discussionsupporting
confidence: 80%
“…Cortisol and 6-P-hydroxycortisol were analysed by HPLC (Lykkesfeldt et al 1994) and the metabolic ratio was calculated according to Ged et al (1989) as:…”
Section: Mephenytoinmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also the case that both endogenous cortisol and alprazolam are substrates for cytochrome P450-3A4 (CYP3A4), which is responsible for metabolism to 6b-hydroxycortisol and 4-and a-hydroxyalprazolam (Ged et al, 1989;von Moltke et al, 1994). There is evidence that CYP3A4 can accommodate more than one substance and that interactions with a particular substrate can impact on the metabolism of the other (Wang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1989). and cortisol (Ged et al, 1989). Screening of a bacteriophage Agtll expression cDNA library using antibodies raised against P450 N F led to the isolation oftwo clones designated NF25 (Beaune et al, 1986) and NFlO (Bork et al, 1989).…”
mentioning
confidence: 99%